Interest in Clinic-Based Financial Services among Low-Income Prenatal Patients and its Association with Health-Related Social Risk Factors. (June 2021) - Liu, Patrick Y.; Bell, Orly; Wu, Olivia; Holguin, Monique; Lozano, Christina; Jasper, Erika; Saleeby, Erin; Smith, Lynne; Szilagyi, Peter; Schickedanz, Adam
Background: Poverty and financial stress affect prenatal health and well-being as well as early childhood development. This study sought to examine interest in clinic-based financial services to address financial stress in low-income, Medicaid-enrolled prenatal patients and its relationship with self-reported social risks. Methods: We conducted a cross-sectional study of patients at a large safety-net prenatal clinic. Participants completed a written survey on interest in linkage to financial services, poverty-related financial stress, difficulty affording social needs, and interest in services to address material hardships. We compared interest in financial and social needs services by level of financial stress using multivariate regression. Results: Respondents (N = 108) were entirely Medicaid-enrolled, with a majority identifying as Hispanic/Latinx (57%) or Black/African American (20%). Sixty-four percent indicated interest in connection to any of the financial services surveyed. Interest was highest in employment (52%), savings and budgeting (49%), job training/adult education (49%), and financial counseling (48%) services. Individuals with high financial stress, compared to those with low financial stress, expressed a higher level of interest in financial services (aRR = 1.61 [95% CI 1.12-2.39]). Interest in financial services was associated with difficulty affording social needs (aRR = 2.24 [95% CI 1.33-4.43]) and interest in services addressing social needs (aRR = 1.45 [95% CI 1.13-1.92]). Conclusion: In this study of low-income, Medicaid-insured prenatal patients, there was a high degree of interest in clinic-based financial services. Integrating financial services into prenatal health care appears to be an approach that low-income patients would be interested in to directly address poverty and financial stress.